Pengaruh Mediasi Work-Family Conflik Terhadap Hubungan Antara Faktor Penentu Work Domain Dan Work Domain Outcomes - Nilawati, Levi; Silalahi, Engelbertha (Universitas Muhammadiyah Yogyakarta, 2014)
The current study suggest that some job insecurity, poor leadership relations, and poor influence at work may also have importance determinant. The relationship between work domain and work outcome domain was analysed on basis of the model in which work domain have an indirect effect on burnout, mediated by work-family coflict This study attempted to look at the influence of determinants and impacts of conflik family and work, taking into account the negative aspects of each of the variables, such as job insecurity, poor leadership relations, and poor influence at work. The implication of the finding and some future research for work-family conflict were also discussed.